P Penetapan Kadar Alkaloid Tanaman Kaluan (Vitex Pinnata L) dengan Tingkatan Fraksi - Ismiadi, Rahmad; Rohama, Rohama; Melviani, Melviani; Mahdiyah, Dede (LPPM Universitas Sari Mulia, 2024)
Background: One of the plants that is often used by people in the interior of Central Kalimantan is the kaluan or halaban plant, where the kaluan or halaban plant is a typical Kalimantan plant that Dayak people usually know as laban. The Kaluan plant is often used by the community as a natural treatment. Kaluan leaves are generally used to treat wounds, scabies, and relieve fever. Kaluan plants have chemical content, the leaves and stem bark contain relatively large amounts of alkaloids, flavonoids, saponins, sterolterpenoids and tannins, which are active compounds that can ward off free radicals.Objective: This research aimed to determine the alkaloid levels in calluan plants (Vitex pinnata L) using fraction levels, distilled water, chloroform, n-hexane.Methods: This research uses an experimental method using the True Experimental type of research which aims to see the comparison of alkaloid levels from kaluan leaf extract (Vitex pinnata Linn) when using N-hexane, chloroform and methanol fractions. The research design used in this study was Randomized block design (random sampling) and compared samples with the 3 fractions used (N-hexane, chloroform, and distilled water).Results: Based on the research that has been carried out, it can be concluded that the total alkaloid content in each, namely, for the n-hexane fraction is 8.03%, for the chloroform fraction it is 7.1%, and for the distilled water fraction it is 2.41%.Conclusion: Based on research, the highest alkaloid content was in the n-hexane fraction, namely 8.03%